(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2021)
The field station of the School for Smallholder Community, Sekaran Village, Kasiman District is one of the places for beef cattle development in Bojonegoro Regency. Sekaran Field Station has several breeds of cattle, including Ongole Crossbred. Ongole Crossbreeds have a large population in the Sekaran School for Smallholder Community with a population of 38%. Evaluation of breeding programs is based on genetic parameters and can be used to obtain the latest information on the successful implementation of breeding programs in a population of livestock. The aim of this study was to evaluate the development program of Ongole Crossbreed cattle at the Sekaran School for Smallholder Community field station using genetic and phenotypic parameters. This study uses a survey method based on questionnaires by conducting interviews with farmers. The data observed were recorded data from 190 heads of Ongole Crossbreeds. The parameters observed were breeding values, genetic and phenotypic correlations, as well as genetic and phenotypic patterns. The results showed that the highest estimation of breeding value in Ongole Crossbred was 5.71 (6 heads) and the lowest was 0.10 (2 heads). The genetic correlation of age at first giving birth, calving distance and empty period ranged from -0.03–0.13. The phenotypic correlation of the three reproductive traits ranged from -0.12-0.09. The genetic patterns of age at first giving birth, calving distance and empty period were -0.97 months/year, -2.51 days/year and 0.05 days/ year, respectively. The phenotypic patterns of the three reproductive traits were 36 months/year, 388 days/year and 84 days/year, respectively. Based on the results of the evaluation of the breeding program using genetic and phenotypic parameters, the development of Ongole Peranakan cattle needs to be continued by implementing good and digital-based management in order to provide success in the Ongole Crossbred development program at the Sekaran field station of the School for Smallholder Community.